Cryogenic thermal conductivity measurements on candidate materials for space missions. (December 2017) - Tuttle, James; Canavan, Edgar; Jahromi, Amir
Highlights: We developed an apparatus for high-precision thermal conductivity measurements. Our apparatus and technique avoid many common systematic measurement errors. We show that the impacts of second-order thermometry effects are insignificant. We present data graphs for ten different material samples. We provide curve fits to the data for the convenience of readers. Abstract: Spacecraft and instruments on space missions are built using a wide variety of carefully-chosen materials. It is common for NASA engineers to propose new candidate materials which have not been totally characterized at cryogenic temperatures. In many cases a material's cryogenic thermal conductivity must be known before selecting it for a specific space-flight application. We developed a test facility in 2004 at NASA's Goddard Space Flight Center to measure the longitudinal thermal conductivity of materials at temperatures between 4 and 300 K, and we have characterized many candidate materials since then. The measurement technique is not extremely complex, but proper care to details of the setup, data acquisition and data reduction is necessary for high precision and accuracy. We describe the thermal conductivity measurement process and present results for ten engineered materials, including alloys, polymers, composites, and a ceramic.